Selective enforcement of regulation - Donghua Chen; Dequan Jiang; Shangkun Liang; Fangping Wang (China Journal of Accounting Research, 2011)
Regulatory agencies may, whether outside of set rules or within their discretion, depart from the original goals or principles set for enforcing the rules, which we term selective enforcement. Taking China, a country in transition, as an example, and using cases and large-sample tests, we present empirical evidence of selective enforcement. The results show that the China Securities Regulatory Commission (CSRC) takes into account whether companies violating the rules have a state-owned background and the strength of that background when investigating and punishing non-compliance. After controlling for the degree of violation, state-owned-enterprises (SOEs) are punished less severely than private companies; and the higher the hierarchy of the SOE in question, the less severe the punishment. It also takes longer for SOEs to be punished. We also find that companies that violate the rules less seriously have a greater tendency to apply for refinancing than those that violate the rules more seriously. This may be because the severity of the violation can affect listed companies' expectations of obtaining refinancing. The analysis and conclusions of this study prove useful in understanding the causes and consequences of selective enforcement in transition economies.
Keywords: G32; G38; G15; 650; Selective enforcement; Government regulation; Violations by listed companies; State-owned companies; Refinancing applications